Potensi Antibakteri Ekstrak Bunga Soka (Ixora coccinea L) terhadap Staphylococcus aureus dan Escherichia coli - Munira Munira; Riska Maisarah; Muhammad Nasir (AcTion: Aceh Nutrition Journal, 2016)
Soka plants (Ixora coccineal L.) often used to treat diarrhea, dysentery and wounds. This study was conducted to determine the effect of soka flower ethanol extract in inhibiting the growth of Staphylococcus aureus and Escherichia coli. This study is experimentally using completely randomized design (CRD) with 4 treatments and 6 repetitions which is distilled water as a control, the ethanol extract of soka flowers concentration are 100%, 75%, and 50%. Microbiological test using the diffusion method of Kirby-Baueur. Phytochemical test results soka ethanol extracts of flowers contain alkaloids, flavonoids, tannins, saponins, and triterpenoid. ANOVA test results ethanol extracts of soka flowers greatly affect the growth of S. aureus and E. coli (P=0.000). Duncan test results an average diameter of inhibition zone for the ethanol extract of soka flowers against S. aureus at a concentration of 100% (14.50 mm) was significantly different from the concentration of 75% (10.33 mm) and concentration of 50% (10.67 mm), while the average diameter of inhibition zone for the ethanol extract of soka flowers against E. coli at 100% (11.00 mm) was not significantly different from the 75% (7.83 mm) and 50% (7.50 mm). The ability of ethanol extract of soka flower in inhibition zone against S. aureus greater than E. coli. Keywords:               Ixora coccinea L., inhibition zone, Staphylococcus aureus and Escherichia coli.